Prevention, Protection and Participation: Children Affected by Armed Conflict - Baillie Abidi, Catherine (Frontiers in Human Dynamics, 2021)
Children are disproportionately impacted in fragile and conflict environments. Through a critical analysis of the ways in which violence is normalized and inherently gendered, this article explores the typology of violence embedded in fragile and conflict environments, the disproportionate impact of forced migration on children affected by conflict, how these interconnected forms of violence are gendered, and the importance of participatory and collective child protection and violence prevention action. Concluding with a discussion of the gaps in peace and security frameworks, the author identifies opportunities to strengthen child protection and recruitment prevention from a gender transformative perspective.